Survei Tingkat Kebugaran Jasmani Siswa IPS Kelas XI SMAN 3 Pamekasan Pasca Pandemi Covid-19 Tahun Ajaran 2022/2023 - Mohammad Ghazi Muhaimin; Dona Sandy Yudasmara; Zihan Novita Sari (Pusat Riset dan Inovasi Nasional, 2024)
The survey research was conducted in conjunction with a quantitative descriptive approach which aims to explain the level of physical fitness of students in class XI IPS at SMAN 3 Pamekasan in the 2022/2023 school year after the Covid-19 pandemic. A total of 40 students were involved as participants in the physical fitness test procedure. Data on the physical fitness test results will be analyzed according to the norms for each physical fitness test contained in the KEMENPORA TKPN. The results showed that the nutritional status obtained by class XI IPS students at SMAN 3 Pamekasan in the 2022/2023 academic year after the Covid-19 pandemic was in the assessment of good dietary quality (ideal) by 90%, but not supported by a level of physical fitness that was within the assessment category is sufficient/moderate with the proportion of the value obtained is 2.0.